2006
DOI: 10.1084/jem.20051342
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan is selectively cleaved at the parenchymal basement membrane at sites of leukocyte extravasation in experimental autoimmune encephalomyelitis

Abstract: The endothelial cell monolayer of cerebral vessels and its basement membrane (BM) are ensheathed by the astrocyte endfeet, the leptomeningeal cells, and their associated parenchymal BM, all of which contribute to establishment of the blood–brain barrier (BBB). As a consequence of this unique structure, leukocyte penetration of cerebral vessels is a multistep event. In mouse experimental autoimmune encephalomyelitis (EAE), a widely used central nervous system inflammatory model, leukocytes first penetrate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
379
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(396 citation statements)
references
References 46 publications
8
379
1
3
Order By: Relevance
“…Since MMP-2 also targets b-DG in vivo (17)(18)(19), its enzymatic activity has been tested on the recombinant b-DG (654-750) and compared with the one displayed by MMP-9. MMP-2 produced four proteolytic fragments (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since MMP-2 also targets b-DG in vivo (17)(18)(19), its enzymatic activity has been tested on the recombinant b-DG (654-750) and compared with the one displayed by MMP-9. MMP-2 produced four proteolytic fragments (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,[35][36][37][38] Studies by Toft-Hansen et al 37 revealed that metalloproteinase enzymes are implicated in leukocyte infiltration in neuroinflammation. Agrawal et al 38 further stated that MMP-9-mediated selective cleavage of β-dystroglycan, which anchors astrocyte endfeet to the astroglial basement membrane, is critical for leukocyte penetration of the parenchymal basement membrane and the damage of BBB.…”
Section: Discussionmentioning
confidence: 99%
“…In EAE and MS, immune cell infiltrates are in great part contained to the perivascular space, and the process of leukocyte migration across the parenchymal BM and astrocyte endfeet appears to be more tightly controlled than the diapedesis across ECs (Engelhardt and Sorokin 2009). In EAE, CD4 þ T-cell infiltration across the parenchymal BM is not laminin dependent, but rather requires focal activation of and matrix metalloproteinases (MMP)-2 and MMP-9 to selectively cleave dystroglycan, affecting the BM stability and integrity (Agrawal et al 2006). Interestingly, parenchymal BM components and other ECM-binding receptors on the astrocyte endfeet remain unaffected, indicating the existence of specific and specialized protective mechanisms under the control of astrocytes and possibly other cells within the NVU (Engelhardt and Sorokin 2009).…”
Section: Ms and Related Disordersmentioning
confidence: 99%